The Obama presidency in the constitutional order : a first look - McNamara, Carol, 1961-; Marlowe, Melanie M. (Rowman & Littlefield Publishers, 2011)
The Obama administration is shaping up to be one of the most consequential in recent American history. In this book, a diverse group of presidential scholars step back from the partisan debate to consider the first two years of the Obama presidency through the lens of the U.S. constitution's theory, structure, and powers. They ask how Barack Obama understands and exercises the President's formal constitutional and informal powers and responsibilities of the president, from foreign policy and public policyto his political leadership of the Democratic party and the nation as a whole.